2014
DOI: 10.1302/0301-620x.96b11.33465
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone density of the proximal tibia as it relates to failure of a total knee replacement

Abstract: The relationship between post-operative bone density and subsequent failure of total knee replacement (TKR) is not known. This retrospective study aimed to determine the relationship between bone density and failure, both overall and according to failure mechanism. All 54 aseptic failures occurring in 50 patients from 7760 consecutive primary cemented TKRs between 1983 and 2004 were matched with non-failing TKRs, and 47 failures in 44 patients involved tibial failures with the matching characteristics of age (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…Based on our findings, there may be low quantities of bone stock in individuals with higher levels of OA-related pain, potentially placing them at risk of inadequate osseo-integration and implant fixation [ 53 ] and possibly implant loosening [ 54 ]. As there is an expected normal decrease in tibial BMD during healing [ 55 ], reduced amounts of tibial epiphyseal bony support structure prior to TKR could compromise implant fixation and success in the early stages, potentially compromising long-term implant success. It may be beneficial to use imaging and complementary image-processing techniques to evaluate preoperative bone density, especially in the commonly overlooked tibial epiphyseal and metaphyseal regions, to compliment customized surgical approaches in patients with higher levels of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, there may be low quantities of bone stock in individuals with higher levels of OA-related pain, potentially placing them at risk of inadequate osseo-integration and implant fixation [ 53 ] and possibly implant loosening [ 54 ]. As there is an expected normal decrease in tibial BMD during healing [ 55 ], reduced amounts of tibial epiphyseal bony support structure prior to TKR could compromise implant fixation and success in the early stages, potentially compromising long-term implant success. It may be beneficial to use imaging and complementary image-processing techniques to evaluate preoperative bone density, especially in the commonly overlooked tibial epiphyseal and metaphyseal regions, to compliment customized surgical approaches in patients with higher levels of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative changes in the periprosthetic bone density in the tibia are closely related to the outcomes of TKA. Several studies [4][5][6][7] have reported a reduction in BMD in the proximal tibia after TKA, which can cause the subsidence of some components, especially of the tibial plateau, and increase the risk of prosthetic loosening and further revision.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative changes in the periprosthetic bone density in the tibia are closely related to the outcomes of TKA [4,5]. Several studies [6][7][8][9] have reported a reduction in BMD in the proximal tibia after TKA, which can cause the subsidence of some components, especially of the tibial plateau, and increase the risk of prosthetic loosening and further revision.…”
Section: Introductionmentioning
confidence: 99%